Pentingnya Perlindungan Hukum dan Pembangunan Ekonomi Atas Pengembangan Teknologi Kecerdasan Buatan - Nur Muharrikatiddiniyah; Elfrida Ratnawati (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Artificial intelligence (AI) is intelligence added to a system, which means the system's ability is developed by humans to manage data and the processed results are used for certain purposes. The era of digitalization is increasingly developing, so that without us realizing it, new discoveries in the fields of electronics, engineering and many other scientific disciplines have been influenced by or use artificial intelligence. Several studies suggest that Europe and the US are pioneer countries in the application of artificial intelligence. Artificial Intelligence/AI has been used in various sectors, such as education, the economy and national defense. AI is implemented from elementary school to high school. In its development, AI has had a significant positive impact on various fields, from industry, health, education, to government. The responsible use of artificial intelligence can be a driving force, to help advance and to realize a sustainable and inclusive society. However, on the other hand, the progress of Artificial Intelligence, technology created to be able to carry out activities in such a way as humans, has become a concern for people's lives as Artificial Intelligence can carry out legal actions or the same legal acts as humans can. In fact, the use of AI is very dependent on the availability, integrity and confidentiality of personal data information in cyber space. Even though it was created with fast and consistent problem solving capabilities, this technology does not have inner awareness or conscience. It is necessary to strengthen legal protection by updating national laws that are adapted to advances in the era of artificial intelligence (AI).